Aging of the Vascular System and Neural Diseases - Watanabe, Chisato; Imaizumi, Tsutomu; Kawai, Hiromi; Suda, Kazuma; Honma, Yoichi; Ichihashi, Masamitsu; Ema, Masatsugu; Mizutani, Ken-ichi (Frontiers in Aging Neuroscience, 2020)
Vertebrates have acquired complex high-order functions facilitated by the dispersion of vascular and neural networks to every corner of the body. Blood vessels deliver oxygen and nutrients to all cells and provide essential transport systems for removing waste products. For these functions, tissue vascularization must be spatiotemporally appropriate. Recent studies revealed that blood vessels create a tissue-specific niche, thus attracting attention as biologically active sites for tissue development. Each capillary network is critical for maintaining proper brain function because age-related and disease-related impairment of cognitive function is associated with the loss or diminishment of brain capillaries. This review article highlights how structural and functional alterations in the brain vessels may change with age and neurogenerative diseases. Capillaries are also responsible for filtering toxic byproducts, providing an appropriate vascular environment for neuronal function. Accumulation of amyloid β is a key event in Alzheimer’s disease pathogenesis. Recent studies have focused on associations reported between Alzheimer’s disease and vascular aging. Furthermore, the glymphatic system and meningeal lymphatic systems contribute to a functional unit for clearance of amyloid β from the brain from the central nervous system into the cervical lymph nodes. This review article will also focus on recent advances in stem cell therapies that aim at repopulation or regeneration of a degenerating vascular system for neural diseases.